2010
DOI: 10.1007/s00228-010-0812-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of paliperidone versus risperidone and clinical effects

Abstract: Based on these results, we conclude that risperidone and paliperidone have a similar therapeutic range and similar intra-individual variability in terms of trough serum levels. For treatment optimization, monitoring of plasma concentrations may be as useful for paliperidone as for risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
3
18
2
3
Order By: Relevance
“…The therapeutic reference ranges as recommended by the TDM group of the AGNP are given in ▶ Table 4. ▶Table 4 Recommended therapeutic reference ranges (consensus), elimination half-life (t1/2) ranges and laboratory alert levels for neuropsychopharmacological drugs and levels of recommendation to use TDM as clinical routine for dose optimization without specific indications (see ▶ [40,110,224,842] Continued.…”
Section: Definitionmentioning
confidence: 99%
“…The therapeutic reference ranges as recommended by the TDM group of the AGNP are given in ▶ Table 4. ▶Table 4 Recommended therapeutic reference ranges (consensus), elimination half-life (t1/2) ranges and laboratory alert levels for neuropsychopharmacological drugs and levels of recommendation to use TDM as clinical routine for dose optimization without specific indications (see ▶ [40,110,224,842] Continued.…”
Section: Definitionmentioning
confidence: 99%
“…Because the lithium groups in the survival experiment exhibited greater urination than did the lithium groups in the proliferation experiment (we hypothesize that this was the result of the longer duration of lithium treatment), we suspect that this affected the rate of paliperidone excretion in these animals (Mannens et al, 1993). Mean peak to trough ratio of paliperidone (Invega) in humans is 1.7 according to manufacturer's instructions (Janssen Pharmaceutica), with the trough 75th percentile of serum concentrations being 52 ng/ml (middle 50th percentile 20 -52 ng/ml) (Nazirizadeh et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…42 Studies with clozapine showed doubtful correlations between blood concentrations and clinical response, but they did identify a concentration threshold cut-off or a therapeutic window to validate the use of therapeutic drug monitoring. [43][44][45][46][47][48][49] No correlation was found between blood levels and clinical effect for risperidone and paliperidone (9-hydroxyrisperidone), [50][51][52][53][54][55][56][57] although an unreplicated study found a therapeutic window. 51 Plasma levels of ziprasidone are unpredictably related to dose and do not correlate with symptom improvement, except for negative symptoms assessed with the PANSS.…”
Section: Discussionmentioning
confidence: 99%